Implementation of the Seven Minute Lecture Program and the Duha Prayer Program in Shaping Student Piety - Muazmis Faridin; Sofwan Aljauhari; Faisal (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Student piety has become a relatively strong issue in Indonesia in the last two decades. This study aims to analyze the implementation of the Seven-Minute Lecture (Kultum) and Duha Prayer Programs in shaping student piety. This study uses a qualitative approach with a literature and field study approach. Data comes from students of the Timika Muslim Community Private High School. The study results indicate that implementing the Kultum Program in shaping student piety involves various activities, including program planning, speaker selection, material preparation, implementation, evaluation, and feedback. Implementing the Duha Prayer Program in shaping student piety involves various activities, including program planning, socialization and education, facilities and infrastructure, implementation, evaluation, and feedback. Internal supporting factors for implementing the Kultum and Dhuafa Prayer programs are the environment, academic activities, extracurricular activities, social interaction, psychological support and counseling, community participation, teaching approaches, skills and characteristics, student relationships, school community involvement, and professional development. Meanwhile, external supporting factors include government initiatives to improve access and quality of education, teacher training programs, international assistance, technology, special programs, and community participation. The government and local governments need to provide support so that the Kultum and Duha Prayer programs to shape student piety can be implemented sustainably.